A Review of Issues in Healthcare Information Management Systems and Blockchain Solutions - Litchfield, A; Khan, A (Association for Information Systems (AIS), 2019)
Healthcare is a data-driven domain where a large volumes of data are created, accessed, stored, and disseminated daily. In this paper, issues such as security, privacy, data transparency, interoperability, data accessibility, user interface issues in healthcare information management systems are presented. In addition, blockchain technology related studies in healthcare information systems are discussed with the aim to find what issues in healthcare system present research opportunities using blockchains.
Keywords: Healthcare data; Healthcare Information Management System issues; Blockchain technology